[PP.36.03]: PREVENTING HEART FAILURE USING MEDICAL INTERVENTION GUIDED BY NTPROBNP. (June 2015) - Dimitriu>, I.>; Raileanu, M.; Calin, C.; Dorobantu, M.; Sinescu, C.
Abstract : Objective: It is well known that NTproBNP is useful in diagnosis of heart failure. This is a pilot study that aims to study the importance of NTproBNP in patients without heart failure(but with conditions at risk of developing heart failure)for guiding treatment to prevent heart failure. Design and method: We included 164 patients who were present at Bagdasar-Arseni Hospital for cardiology consultation, during one year, with the following conditions: hypertension, diabetes, ischemic heart disease, valvular disease, arrhythmias We excluded patients who are already diagnosed with heart failure, left ventricular systolic or diastolic dysfunction or who had current symptoms of heart failure. We randomized patients into 2 equal groups: a control and an intervention group. In the intervention group patients were treated according to the NTproBNP Patients who had NTproBNP < 125 pg / dl (36 patients) received standard treatment for their symptoms. Patients who had NTproBNP > 25 pg / dl (46 patients) were the ones on which we intervened to prevent heart failure.They were investigated by cardiac ultrasound and other specific tests for each case (blood test, stress test, ECG monitoring/24 h). After completing medical balance, each patient received specific treatment. Patients in the control group received standard treatment for their symptoms regardless of the NTproBNP value Results: After one year, the end points were: diagnosis of cardiac failure, left ventricular systolic or diastolic dysfunction, patient death from any cause, the rate of hospitalizations for cardiovascular pathology. After a year in the control group were 18(21, 9 %)patients who developed heart failure compared to 10(12, 1%) patients in the intervention group. 26(31, 7 %)patients were diagnosed with left ventricular systolic dysfunction, compared to 26(31, 7 %) in the intervention group. Also, and rate of admissions for heart disease was higher in the control group 28(34, 1%) versus 17(20, 7%) in the intervention group. Conclusions: Patients in the intervention group, in which the value of NTproBNP was used in choosing therapeutic management, have lower rate of heart failure or cardiovascular events than patients in the control group. This value NTproBNP in patients without heart failure can detect patients at risk of developing heart failure. And more, medical intervention guided by NTproBNP can prevent or delay heart failure in these patients